Moja autobiografia duchowa: powołanie teologa naturalnego - Swinburne, Richard (Poznańskie Studia Teologiczne, 2011)
The author describes his intellectual development and academic pursuits starting from his undergraduate studies at Oxford University in mid-1950s up to the present day, in the perspective of his attempts to resolve the conflict between a materialistically oriented scientific worldview and the worldview of traditional Christianity. In time, he came to recognize the conflict as a problem of distinguishing between levels of explanation or points of terminating an explanation. To deal with this problem adequately, he adopted as his own the program of natural theology laid down by St. Thomas Aquinas in his Summa Theologiae, where Aquinas provided good arguments in favor of the Christian doctrine taking as his starting point the most general phenomena of experience and using the best secular knowledge of his day. Thus Swinburne’s program of natural theology consisted in using the criteria used in modern natural science and historical inquiry for the probable truth of a suggested explanation, analyzed with the careful rigor of modern philosophy, to show the meaningfulness and probable truth of Christian theology. Scientific explanation explains phenomena in terms of prior states of affairs and natural laws; whereas personal explanation explains phenomena in terms of the powers and purposes of agents. Christian metaphysics explains the operation of scientific explanation in explaining why there are states of affairs at all and why the most fundamental natural laws have the character they do, in terms of the power and purposes of God, and in particular his purpose that humans should have a free choice of the kind of persons they are to be. Swinburne extends this model of explanation to show that our historical evidence about the life of Christ makes it very probable that Christ was (and so is) God Incarnate who rose from the dead.